Remote Data Monitoring Improves Distribution System Efficiency and Maintenance. Issue 2 (1st February 2016) - Feffer, Adam; Baker, Dave; Moore, Randy; Wagner, Travis; Gresehover, Brian
Abstract : Water and wastewater utilities are drawing on advances in distribution monitoring technologies to improve their distribution systems. Today's remote data monitoring tools efficiently and accurately collect pressure and other data, enabling faster response times.